A cosmopolitan jurisprudence : essays in memory of H. Patrick Glenn - Dedek, Helge, 1973-; Glenn, H. Patrick (Cambridge : Cambridge University Press, 2022)
H. Patrick Glenn (1940-2014), Professor of Law and former Director of the Institute of Comparative Law at McGill University, was a key figure in the global discourse on comparative law. This collection is intended to honor Professor Glenn's intellectual legacy by engaging critically with his ideas, especially focusing on his visions of a 'cosmopolitan state' and of law conceptualized as 'tradition'. The book explores the intellectual history of comparative law as a discipline, its attempts to push the objects of its study beyond the positive law of the nation-state, and both its potential and the challenges it must confront in the face of the complex phenomena of globalization and the internationalization of law. An international group of leading scholars in comparative law, legal philosophy, legal sociology, and legal history takes stock of the field of comparative law and where it is headed.
How to do comparative law : some lessons to be learned / Mauro Bussani -- The 'comparative method' at the roots of comparative law / Giorgio Resta -- The value of micro-comparison / John Bell -- Sociocultural challenges for comparative legal studies in mixed legal systems / Esin Or uc u -- Breaking barriers in comparative law / Michele Graziade -- Too much information / Martin Krygier -- Legal systems as legal traditions / Catherine Valck -- Learning from Patrick Glenn : tradition, change, and innovation / David Nelken -- The Sunni legal tradition : an overview of pluralism, formalism, and reform / Ahmed Fekry Ibrahim -- Commensurability, comparative law, and Confucian legal tradition / Marie Seong-Hak Kim -- The school of Salamanca : a common law? / Thomas Duve -- The un-common law / Vivian Grosswald Curran -- The fabric of normative translation in law / Ko Hasegawa -- Statehood as process : the modern state between closure and openness / Gunnar Folke Schuppert -- Cosmopolitan Attachments/ Neil Walker.
Title from publisher's bibliographic system (viewed on 10 Dec 2021).
Keywords: Law